COVID-19-Related Changes to Pregnant People's Work-Plans Increase Prenatal Depression - Sherin, Margaret; Gildner, Theresa E.; Thayer, Zaneta M. (Frontiers in Global Women's Health, 2021)
The COVID-19 pandemic has caused unprecedented rates of unemployment in the United States. Pregnant workers may be especially affected as they are over-represented in low-wage service and hospitality industries impacted by the pandemic. We surveyed an online convenience sample of currently working pregnant people living in the U.S. (n = 1,417) to determine whether COVID-19-related changes to how long individuals planned to work during their pregnancy, and uncertainty about these changes, were associated with prenatal depression. As hypothesized, both COVID-19-related work-plan changes (OR = 1.81, 95% CI 1.36–2.42, p < 0.001) and uncertainty about the precise nature of these changes (OR = 2.62, 95% CI 1.14–6.0, p = 0.022) were associated with significantly higher odds of a clinically-significant depression score. These effects appeared to be even greater among individuals who continued working outside the home during the pandemic. Since the U.S. is one of the few countries in the world that does not guarantee paid parental leave, pregnant people may be forced to choose between keeping their jobs and risking infection during the COVID-19 pandemic. Our results demonstrate a need for immediate suspension of the eligibility requirements for the Family and Medical Leave Act and/or universal access to both paid family leave and prenatal depression screening. This would help to alleviate these concerns and provide pregnant people with more options while preserving their employment status and financial security.